3D Printing Geometric Scaffold Design Variation of Injectable Bone Substitutes (IBS) Pa - Hikmawati, Dyah; Nugraheni, Sarda; Aminatun, Aminatun (Universitas Airlangga, 2020)
3D printing technology application in tissue engineering could be provided by designing geometrical scaffold architecture which also functionates as drug delivery. For drug delivery scaffold on bone tuberculosis, the cell pore of the geometric design was filled with Injectable Bone Substitutes (IBS) which had streptomycin as anti-tuberculosis. In this study, scaffolds were synthesized in three cells geometric filled by Injectable Bone Substitutes (IBS), Hexahedron, Truccated Hexahedron, and Rhombicuboctahedron, which had 2.5 mm x 2.5 mm x 2.5 mm size dimension and 0.8 mm strut. The final design was printed in 3D with polylactic acid (PLA) filament using the FDM process (Fused Deposition Modelling). The composition of IBS paste was a mixture of hydroxyapatite (HA) and gelatine (GEL) 20% w/v with a ratio of 60:40, streptomycin 10 wt% and hydroxypropyl methylcellulose (HPMC) 4% w/v. It was then characterized using Fourier-transform infrared spectroscopy (FTIR). Scaffold–paste characterization was included pore size test of 3D printing result before and after injected using Scanning Electron Microscope SEM, porosity test, and compressive strength test. The result showed that the pore of scaffold design was 1379 µm and after injected with IBS paste, the pore leaving 231.04 µm of size. The scaffold with IBS paste porosity test showed ranges between 40,78-70,04% while the compressive strength of before and after injected ranges between 1,110-634 MPa and 2,217-6,971 MPa respectively. From the test results, the scaffold 3D printing with IBS paste in this study had suitable physical characteristics to be applicated on cancellous bones which were infected by tuberculosis.